The influence concentration gel agent propolis combination of mulberry leaf on the growth of the bacteria Propionibacterium acnes - Prayitno Setiawan; Nurfitria Junita (Sasambo Journal of Pharmacy, 2022)
This research was carried out with the aim of determining the inhibitory power of the combination gel of propolis extract and mulberry leaf extract against Propionibacterium acnes bacteria and determining the concentration of propolis extract that provided the greatest inhibitory power against the test bacteria. The research method includes the extraction of mulberry leaves by maceration using 70% ethanol as a solvent and the propolis extract used is a ready-to-use extract. The formulations were designed with various concentrations of propolis (0.5%, 1%, 1.5%) and 0.5% mulberry leaf concentration. Testing the antimicrobial activity of propolis extract in combination with mulberry extract in gel preparations against the growth of Propionibacterium acnes bacteria was carried out using the agar diffusion method. The results showed that the average diameter of the inhibition area at 0.5% concentration was 36.87 mm, at 1% concentration was 44.557 mm and at 1.5% concentration was 45.97 mm, positive control was 49.21 mm. Based on the data obtained, it is concluded that the gel formula with a propolis concentration of 1.5% is the preparation with the largest zone of inhibition.